Lead from the future : how to turn visionary thinking into breakthrough growth - Johnson, Mark W.; Suskewicz, Josh (Boston, MA : Harvard Business Review Press, 2020)
'From the author of the groundbreaking book Reinvent Your Business Model, a new approach for thinking about the future and turning your most promising and creative ideas into reality. We all know visionary leaders when we see them. In business, they are last-name-only disrupters like Jobs, Bezos, and Hastings, and, in politics, they are such transformative figures as Mandela and FDR. They're bold and prophetic and at the same time pragmatic. They don't just promote change--they drive it, and they inspire and mobilize others to do the same. Although these leaders possess innate qualities that make them extraordinary, what truly sets them apart is their ability to turn their visions into action. In this timely and compelling book, Mark W. Johnson, cofounder of Innosight, and Josh Suskewicz, an Innosight partner, lay out a new and innovative approach to developing and executing the visionary ideas that drive breakthrough growth. This approach includes: Developing a mind-set that enables you to look beyond the present Translating your vision into a strategic plan that your team can align around and commit to Instilling visionary thinking into the processes and culture of your whole organization As practical as it is inspiring, Lead from the Future is the guide you and your team need in order to think clearly, creatively, and expansively, and then act decisively about what comes next'--
Introduction. Lead from the future -- Part I. Principles: The perils of the present forward fallacy -- Thinking from the future back -- Part II. Application: Creating an inspiring and actionable vision -- Converting vision to strategy -- Programming and implementing your strategy -- Part III. Institutionalization: Infusing future back thinking into leadership teams -- Infusing future back thinking into your organization -- Part IV. Broader implications: Moving beyond the business world -- Epilogue: A vision for 21st century management.
Includes index.
Buku bacaan asas prasiswazah 2023/2024 Fakulti Ekonomi Pengurusan.
Keywords: Transformational leadership; Forecasting; Creative ability in business; Success in business